ANALISIS STRUKTURALISME GENETIK NOVEL PERAHU KERTAS KARYA DEWI LESTARI - Sundari, Iis (Diksa : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2015)
The research on novel Perahu Kertas by Dewi Lestari, is a research using Genetic Strukturalisme approach. This research aims to determine the intrinsic and extrinsik elements of the novel. The method using qualitive descriptive. The focus of the research are (1) the structure of Perahu Kertas novel that creates its meaning as a whole, (2) social life of the author Dewi Lestari associated with the novel, (3) Indonesian historical bacground or social events conditioned the birth of this novel. The result showed that loving problem, morality, social, education, and profession of the themes of this novel Perahu Kertas. As someone who is konwledgeable, its write gives an understanding about humanity and morality values to people. According to sociological view of Dewi Lestari in this novel and the background of history behind the emergence of Perahu Kertas , a novel by Dewi Lestari.